2017
DOI: 10.12681/jhvms.15009
|View full text |Cite
|
Sign up to set email alerts
|

Organic acids in pig and poultry nutrition

Abstract: Η χρήση των οργανικών οξέων στη διατροφή του χοίρου και των πτηνών Organic acids in pig and poultry nutrition Η. Α. Γιάννενας Giannenas I. A.ΠΕΡΙΛΗΨΗ. Σε αυτήν xn βιβλιογραφική εργασία εξετάστηκε η χρήση των οργανικών οξέων ως πρόσθετων υλών ζωοτροφών στη διατροφή του χοίρου και των πτηνών. Σκοπός της εργασίας ήταν η εκτίμηση της επίδρασης των οργανικών οξέων και των αλάτων τους στις αποδόσεις του χοίρου και των πτηνών, η περι γραφή των οργανικών οξέων που χρησιμοποιούνται στη διατροφή των ζώων, ο τρόπος χορήγ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…However, we should keep in mind that MIC value is only indicative since it represents only the direct effect of the tested product against the tested pathogen. It does not consider the indirect effect that could be had on the intestinal microbiota, feed ingredients, immune system, and intestinal digesta [ 25 , 57 , 59 ]. In addition, the biocide efficiency could be affected by various parameters, including concentration, pH, formulation, temperature, presence of organic matter and biofilms in the drinking lines, as well as contact time [ 54 , 55 , 61 ].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…However, we should keep in mind that MIC value is only indicative since it represents only the direct effect of the tested product against the tested pathogen. It does not consider the indirect effect that could be had on the intestinal microbiota, feed ingredients, immune system, and intestinal digesta [ 25 , 57 , 59 ]. In addition, the biocide efficiency could be affected by various parameters, including concentration, pH, formulation, temperature, presence of organic matter and biofilms in the drinking lines, as well as contact time [ 54 , 55 , 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…For some products, such as water acidifiers and glyceride blends, chemical formulations and manufacturer recommendations are promising for additional indirect antimicrobial effects under in vivo applications [ 25 , 57 , 59 ], whereas for other products, such as hydrogen peroxide-based formulas, no prior data are available. It is reported that applying organic acid blends through drinking water could reduce the pH in the bird’s crop and thus serve as an effective barrier in the growing and spreading of pH-sensitive bacteria like Salmonella and Campylobacter [ 19 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations